Peran Guru Dalam Menangani Dampak Negatif Media Sosial Tiktok Pada Remaja Di Madrasah Aliyah Roudlotul Mutaalimin Kecamatan Kanigoro Kabupaten Blitar - Ika Setiawati; Muhammad Rizal Rifa`i; Amit Dana Ikmah; Septyan Tenti Asih (Universitas Pangeran Diponegoro Nganjuk, 2026)
TikTok is an application designed for entertainment and allows users to record, edit, and upload videos to various social media platforms. This application is a contemporary music video social platform equipped with various interesting on-screen features such as stickers and filters. The TikTok application also has effects that users can use to create short videos to make their videos more interesting. Furthermore, the TikTok application also provides background music from various famous or popular artists. TikTok users are free to imagine according to their interests and share them with other friends and even around the world. The type of research used by the author is qualitative, employing a descriptive study approach. While data collection requires observation, interviews, and documentation methods. In analyzing the collected data, the researcher used qualitative descriptive analysis. From the results of this study, we conclude that: 1). Lack of direct interaction with people in the surrounding environment and lack of concern for people in the surrounding environment and students are exposed to a lot of useless, negative content on the TikTok application, which some people consider to be part of entertainment as a means of showing off to follow current trends so that many posts lower the morals of students due to the lack of guidance from those closest to them. 2). Efforts made by teachers of MA Roudlotul Mutaalimin appealed to and strictly limited the use of cellphones in the Islamic boarding school and at school. As for students from outside the Islamic boarding school or from the area around the madrasah, they were given restrictions on cellphone use at school. In addition, they were also given direction and guidance in the use of cellphones, especially in the use of the TikTok application.